If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(x + -1) = 5(x + -8) Reorder the terms: 12(-1 + x) = 5(x + -8) (-1 * 12 + x * 12) = 5(x + -8) (-12 + 12x) = 5(x + -8) Reorder the terms: -12 + 12x = 5(-8 + x) -12 + 12x = (-8 * 5 + x * 5) -12 + 12x = (-40 + 5x) Solving -12 + 12x = -40 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -12 + 12x + -5x = -40 + 5x + -5x Combine like terms: 12x + -5x = 7x -12 + 7x = -40 + 5x + -5x Combine like terms: 5x + -5x = 0 -12 + 7x = -40 + 0 -12 + 7x = -40 Add '12' to each side of the equation. -12 + 12 + 7x = -40 + 12 Combine like terms: -12 + 12 = 0 0 + 7x = -40 + 12 7x = -40 + 12 Combine like terms: -40 + 12 = -28 7x = -28 Divide each side by '7'. x = -4 Simplifying x = -4
| 4(x-8)=2(x+6) | | 9(x+6)=8(x+8) | | 2(3-x)+3(x-5)=0 | | 2(1-x)=3(2-x) | | 3(x-10)=2(x-15) | | (4-5i)(5-i)= | | 3(x-10)=3(x-15) | | 10(x+3)=5(x+4) | | 12(x+3)=7(x+8) | | 7x-6=4(5+5x) | | 2-4x=5(2x-8) | | mr=(1.97-(x+1)) | | 11(1-x)=44 | | 2(3+x)=8 | | 9c+c*2c-3=9 | | 6x^3-9x-x^5=0 | | -11(x-8)=44 | | 9(x-5)=2x-24 | | 2x+7y=-3 | | 4(x-6)=0 | | 7(5-x)=-14 | | 3(1-x)=6 | | 8(x+2)=-32 | | 2x-3=-3x+12 | | X=1-2.5y | | -5(x+7)=-40 | | 6x+15y=6 | | 21-4x=45 | | -10(x+1)=10 | | -2x^4+4x^3=0 | | 9(x-15)=9 | | 32-6x=53 |